THE IMPLEMENTATION OF THE BANDONGAN METHOD IN THE STUDY OF FIQH BOOKS AT THE RIYADHUL AWAMIL BOARDING SCHOOL - Zuhri, Safudin; Fazrurrakhman (Journal of Educational Administration, 2022)
Boarding school is an institution of education in Indonesia and can contribute to the development of human resources and education for the general public in Indonesia. One of them is a boarding school in Banten Province, Serang city, named Riyadul Awamil. Riyadh Lamil Islamic Boarding School has always kept its commitment to producing cadres of the Ummah and cadres of the nation to make the human resources in it, especially as the next generation of 'alimin ulama' and generally able to practice the results of their learning in everyday life. The purpose of this study was to determine the implementation, the ability of students, and the implementation of the bandongan method in the study of fiqh at the Riyadhul Layil Islamic Boarding School. This study uses a descriptive qualitative research method whose results are obtained through interviews and field observations. In the implementation of the bandongan strategy in the study of the book of fiqh at the Riyadhul layil Islamic boarding school, it was carried out well and there was practice from the theory contained in the contents of the fiqh so that it could be easily understood and understood by the students